Dried distiller’s grains in steam-flaked corn finishing diets with decreased roughage levels - M.L. May; M.J. Quinn; K.K. Karges; M.L. Gibson; Brandon E. Depenbusch; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2008)
Distiller's grains are the primary coproduct derived from fuel ethanol production. As the fuel ethanol industry expands into the High Plains, distiller's grains are becoming increasingly available as an alternative feed for livestock. Optimizing the use of distiller's grains in flaked grain rations is important to maintaining a competitive advantage among feedlot producers in this region. Because distiller's grains are relatively high in fiber, it is conceivable that the level of roughages in feedlot diets could be reduced when distiller's grains are fed to cattle. Roughages normally have low energy density; therefore, the cost per unit of energy from roughages usually is relatively high compared with cereal grains or grain co-products. If the use of distiller's grains would allow roughage levels to be decreased in finishing diets without deleterious consequences for health or performance, this generally would be viewed as a positive attribute. Our objective was to evaluate performance of feedlot cattle fed diets with and without distiller's grains, and assess the effect of reducing the level of added roughage in diets containing distiller's grains.
Keywords: Cattlemen' s Day; 2008; Kansas Agricultural Experiment Station contribution; no. 08-212-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 995; Beef; Cattle; Corn finishing diets; Decreased roughage levels